2015
DOI: 10.1007/s10653-015-9718-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction of potentially toxic elements by Indian mustard, rapeseed, and sunflower from a contaminated riparian soil

Abstract: The objective of this study was to quantify the phytoextraction of the potentially toxic elements Al, As, Cd, Co, Cr, Cu, Mo, Ni, Pb, Se, V, and Zn by Indian mustard, rapeseed, and sunflower from a contaminated riparian soil. To achieve this goal, a greenhouse pot experiment was established using a highly contaminated grassland soil collected at the Wupper River (Germany). The impact of ethylene-diamine-tetra-acetic acid (EDTA), humate (HK), and phosphate potassium (PK) on the mobility and uptake of the elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…These results indicated that sunflower can grow on soil contaminated with Cr, Cu, and Zn, and it can also accumulate large amounts of Zn [22]. Sunflower is relatively resistant to high Zn soil concentrations; therefore, it can be used for Zn phytoextraction of moderately contaminated soil (approximately 200 mg Zn kg −1 soil) [23].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that sunflower can grow on soil contaminated with Cr, Cu, and Zn, and it can also accumulate large amounts of Zn [22]. Sunflower is relatively resistant to high Zn soil concentrations; therefore, it can be used for Zn phytoextraction of moderately contaminated soil (approximately 200 mg Zn kg −1 soil) [23].…”
Section: Discussionmentioning
confidence: 99%
“…in paper industry as a filler and pigment for coating, in food industry as a hardener and food dye (E 170), in agriculture for fertiliser manufacturing, in metallurgy as a flux in ladle desulphurisation, in construction, chemical, cosmetics and pharmaceutical industries. The research has been carried out in recent years on the possibility to use eggshells as a catalyst in the processes of biodiesel production [1,2], lactose isomerisation [3], dimethyl carbonate synthesis [4] and as a sorbent in water treatment processes [5,6], immobilisation of heavy metals in soils [7,8], CO 2 binding (removing) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Phytoextraction is recommended as one option for reducing toxic metal content, as the technology is perceived to be ecofriendly, effective, and affordable (Shaheen and Rinklebe, 2015;Antoniadis et al, 2017). Phytoextraction heavy metals had received increasing attention in recent years as an alternative to physical and chemical methods of decontamination in which heavy metals accumulating plants and appropriate soil amendments were used to transport and concentrate heavy metals from the soil into the aboveground shoots (Nowack et al, 2006;Vamerali et al, 2012).…”
Section: Introductionmentioning
confidence: 99%